2018
DOI: 10.12691/ajer-6-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Economic Growth Nexus in Mozambique: 1975-2016

Abstract: This study explores the relationship between energy consumption and economic growth in Mozambique for 1975-2016 period, using Vector error correction model and Granger causality test. The VECM result suggests the existence of unidirectional long-run relationship running from EC to GDP. Granger causality test proposes that energy consumption Granger causes economic growth. Therefore, in Mozambique is indispensable an energy consumption development policy to stimulate economic growth. Mozambique has plentiful en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Isaiah et al (2015) with the aid of the Kalman Filter Approach on time series data spanning from 1995 to 2012 found that economic growth is the main driver electricity consumption in Lesotho. Furthermore, the studies of Bildirici (2013), Nindi and Odhiambo (2014), Sharmin and Khan (2016), Bay (2018) and Huo and St Aubyn (2021) explored the relationship between electricity consumption and economic growth in Mozambique utilising ARDL, VECM and VAR models. Majority of these studies are of the view that electricity consumption enhances economic growth, while Ramadhan et al (2016) with the aid of OLS model recommend an improvement in the sectors of electricity supply to maintain long run economic growth.…”
Section: Studies From Sadc Regionmentioning
confidence: 99%
“…Isaiah et al (2015) with the aid of the Kalman Filter Approach on time series data spanning from 1995 to 2012 found that economic growth is the main driver electricity consumption in Lesotho. Furthermore, the studies of Bildirici (2013), Nindi and Odhiambo (2014), Sharmin and Khan (2016), Bay (2018) and Huo and St Aubyn (2021) explored the relationship between electricity consumption and economic growth in Mozambique utilising ARDL, VECM and VAR models. Majority of these studies are of the view that electricity consumption enhances economic growth, while Ramadhan et al (2016) with the aid of OLS model recommend an improvement in the sectors of electricity supply to maintain long run economic growth.…”
Section: Studies From Sadc Regionmentioning
confidence: 99%